"I Didn't Feel Treated as Mental Weirdo": Primary Findings on Helpful Relationship Characteristics in Suicide Attempt Health Care in Lithuania. (January 2022) - Latakienė, Jolanta; Mastauskaitė, Greta; Geležėlytė, Odeta; Mažulytė-Rašytinė, Eglė; Rimkevičienė, Jurgita; Skruibis, Paulius; Michel, Konrad; Gysin-Maillart, Anja
This article aims to investigate helpful relationship characteristics in suicide attempt health care. Semistructured interviews with seven participants (five women and two men; meanage = 26) were conducted after a suicide attempt. All participants took part in the Attempted Suicide Short Intervention Program (ASSIP). Findings revealed the necessity of an egalitarian, attentive, benevolent, and competent relationship with health-care specialists. Coercive clinical management was considered disrespectful, while the needs for physical safety and freedom were expressed. A suicide-specific treatment program in addition to standard care was considered helpful, in particular the development of warning signs and safety strategies.